IMPLEMENTASI PENGGUNAAN APLIKASI SIPIR DALAM MENINGKATKAN KUALITAS PELAYANAN KUNJUNGAN DI RUMAH TAHANAN KELAS IIB BANGKALAN - Muhammad Daffa Abiyu Anubawa; Andi Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to evaluate the implementation of the SIPIR application in enhancing the quality of visitation services at the Bangkalan Class IIB Detention Center. Employing a qualitative descriptive approach, this research analyzes data collected through in-depth interviews, observations, and document analysis. The findings reveal that the SIPIR application has contributed positively to the efficiency of visitation scheduling. However, the implementation of this application still faces several challenges, such as insufficient socialization to users, limited features, and dependency on adequate technological infrastructure. Furthermore, the study identifies factors that support the successful implementation, such as management support, staff involvement, and the existence of standard operating procedures. This study concludes that the SIPIR application has great potential to improve the quality of visitation services in correctional facilities. Nevertheless, continuous efforts are needed to overcome the existing challenges and maximize the benefits of this technology.